Fruit peel waste as a novel low-cost bio adsorbent - Pathak, Pranav D.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Reviews in Chemical Engineering, 2015)
Fruit peel waste (FPW) is abundantly available from the agricultural and food processing industry and has been studied in recent past as an adsorbent. This paper critically reviews the reported work and investigates various FPW-pollutant systems. The study includes statistics of FPW generation, modification, characterization, adsorption ability, recovery/regeneration, and modeling (isotherms, kinetics, and thermodynamics) of batch adsorption. It is found that orange and banana peels are the most extensively studied adsorbents, whereas Pb2+ and methylene blue are the most efficiently removed pollutants, the Langmuir and Freundlich adsorption isotherms provide the best fit in most of the cases, and in general, pseudo-second-order kinetics is followed. There are very limited column studies and no report on commercial plant. Though the reproducibility of the results is poor, FPW has a great potential in the wastewater treatment due to its abundant and cheap availability. FPW can be used for removal of heavy metals and dyes; however, removal of organic and gaseous impurities needs further investigation.
Keywords: adsorbent; Adsorption; fruit peel waste; organic and inorganic pollutants; wastewater